Analysis of temperature distribution in disc brakes - Mohd Amin, Azriszul (2007)
Disc brake have been used for many years and still improving in terms of it temperature reach. Many methods have been introduced in order to simulate and predicting the temperature reach of the disc brake (i.e. Lumped analysis, one dimensional analytical method, two dimensional numerical, and three dimensional numerical method). These numerical simulations are range from finite difference to finite elements with their own assumptions. In this report three independent directions of heat flows is determining in order to find it importance in the solution accuracy of temperature reach in brake disc by using Normalizing and order of magnitude analysis which have been introduced by Ludwig Prandtl in his analysis of fluid flow. The results of order of magnitude will be validated with finite difTerence simulations.